Spanish Doctoral Dissertations on the Properties of Materials in Engineering - Melero-Bolaños, Juan Carlos; Maz-Machado, Alexander; León-Mantero, Carmen María; Rodríguez-Baiget, María Josefa (International Journal of Engineering Pedagogy (iJEP), 2024)
We present a bibliometric study of engineering doctoral dissertations focusing on the properties of materials. The study exhaustively examines the production of doctoral theses on material properties in the field of engineering at Spanish universities from 1977 to 2022. The main objective is to analyse the volume and temporal distribution of these theses, explore their production by authors and directors considering gender, and identify the most common descriptors in the research. Technological innovation and progress in engineering materials are essential for social welfare, economic competitiveness, and international cooperation, highlighting the significance of these studies. The results reveal a total of 508 valid theses after a meticulous filtering process, with a notable increase in production post-1998, particularly during 2011–2020. The study highlights the limited presence of women in both authorship and direction of these, indicating male dominance in the field. However, there is an increasing trend of female participation in these academic areas. This study offers detailed insights into the trends and composition of doctoral research in materials engineering in Spain, pointing to important gender dynamics and research themes.